Atom-economical and scalable asymmetric synthesis of daridorexant key starting material (S)-2-methylproline via the memory of chirality - Bhatt, Gaurang J.; Kumar, Shubham; Mhaske, Santosh B. (Organic Process Research & Development, 2025)
alpha-Methylproline is a key starting material (KSM) for important drugs, such as Daridorexant, Veliparib, Trofinetide, Enlicitide chloride, and Usnoflast. A practical and scalable asymmetric synthesis of (S)-2-methylproline and its derivatives has been disclosed here using a diketopiperazine intermediate-based strategy that leverages the memory of chirality. Commencing from an inexpensive starting material, l-proline, it proceeds through dimerization and alkylation, followed by hydrolysis under mild conditions, avoiding column chromatography to furnish enantiomerically pure (S)-2-methylproline.HCl, which was also converted to (S)-Boc-2-methylproline and (S)-2-methylproline methyl ester.HCl. In contrast to prior multistep approaches, which rely on expensive chiral auxiliaries and hazardous reagents, this concise three-step route offers operational simplicity, scalability, and superior stereochemical control, making it an attractive method for the synthesis of proline-derived building blocks for peptidomimetics and pharmaceutical applications.
Keywords: alpha-methylproline; atom economy; memoryof chirality; Stereoselective

Organophotoredox-catalyzed decarboxylative C-O/N/S bond formation: access to ampakine APIs and quinazolinone alkaloids - Sonavane, Sameer R.; Kale, Tushar B.; Bhatt, Gaurang J.; Mhaske, Santosh B. (Organic Letters, 2025)
This study describes a novel and general protocol featuring organophotoredox-catalyzed intramolecular decarboxylative construction of carbon-heteroatom (oxygen, nitrogen, and sulfur) bonds, enabling direct access to ampakine APIs (CX-614 and CX-554), quinazolinone alkaloids (deoxyvasicinone and mackinazolinone), and thiazinone scaffolds as well as their congeners with broad functional group tolerance and scalability. Mechanistic studies suggest a radical-polar crossover pathway via single-electron oxidation.